Positioning an Agenda on a Loving Pedagogy in Second Language Acquisition: Conceptualization, Practice, and Research - Wang, Yongliang; Derakhshan, Ali; Pan, Ziwen (Frontiers in Psychology, 2022)
Second/foreign language teaching has been found as one of the most emotional professions worldwide. To generate optimal academic outcomes and run an effective education, teachers and students’ emotions and feelings must be positively cared for. Given the significance of emotions in L2 education, many studies have followed positive psychology (PP) and examined various positive constructs. Nevertheless, love, as a PP variable, has been ignored in education due to its cultural/religious sensitivities. Trying to dispel the myths, recently, a new trend called a “loving pedagogy” has started to find itself a place in second language acquisition (SLA) research and practice. Yet, proposing a model of its application and an agenda for its research has been overlooked by scholars in this domain. Motivated by this lacuna, this research article provided the conceptualization, definitions, research bases, practical models, and implications of a loving pedagogy for SLA practitioners and future researchers.